If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 42 = -6x + 18 Reorder the terms: 42 + 2x = -6x + 18 Reorder the terms: 42 + 2x = 18 + -6x Solving 42 + 2x = 18 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 42 + 2x + 6x = 18 + -6x + 6x Combine like terms: 2x + 6x = 8x 42 + 8x = 18 + -6x + 6x Combine like terms: -6x + 6x = 0 42 + 8x = 18 + 0 42 + 8x = 18 Add '-42' to each side of the equation. 42 + -42 + 8x = 18 + -42 Combine like terms: 42 + -42 = 0 0 + 8x = 18 + -42 8x = 18 + -42 Combine like terms: 18 + -42 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 18-(-12)+(-8)= | | y=10(5)-1 | | d-3=-11 | | 8/42 | | y=10(1)-1 | | 1x2+3-4/2 | | 23+X=-85 | | 0=-16t^2+20t-4 | | y=10(0)-1 | | 5x+18=-4x+36 | | y=10(-1)-1 | | 5y-15=9y-19 | | y=10(-1)x-1 | | 16+3x=37 | | n/9=-5 | | 36-44+(-15)= | | 0=-16t^2-16t+60 | | y=-3(3)+3 | | 352/16=x-22 | | x+(5x-28)=180 | | y=-3(-3)+3 | | y(2y+3)=0 | | 0=-16t^2+1600 | | 20=a-(-8) | | (2x^2)+8x+11=0 | | 3(2g+12)=51+3g | | -1.3+y/7=-18.8 | | -7+x=4x+17 | | (y+3)(y+2)=0 | | 4n+3n=5(2-2n) | | 1/5-5m | | y/2+3=11 |